Relationship between forehead motion and the shape of forehead lines—A 3D skin displacement vector analysis. (8th July 2019) - Frank, Konstantin; Freytag, David L.; Schenck, Thilo L.; Green, Jeremy B.; Trovato, Alexa; Barade, Hassan; Rosamilia, Gianna; Lachman, Nirusha; Giunta, Riccardo E.; Cotofana, Sebastian
Abstract: Objective: Neuromodulator injections of the forehead are often performed using standardized protocols. This study was designed to identify the individual skin motion pattern of the forehead and to relate this pattern to the underlying frontalis muscle morphology to offer guidance for neuromodulator placement. Material and Methods: Thirty‐seven healthy volunteers (29 Caucasians, six African Americans, two Asians) with a mean age of 39.84 ± 14.4 years [range: 22‐73] were enrolled. 3D images of the forehead were analyzed using a Vectra H1 camera system computing skin displacement vectors between the noncontracted and the maximally contracted forehead of the volunteers. Relationships between the shape of the horizontal forehead lines (straight vs wavy) and the forehead motion pattern were calculated. Results: Independent of age or gender, a greater forehead motion angle was associated with the presence of wavy forehead lines 21.34°± 5.9 with P  < 0.001, whereas straight forehead lines were associated with a smaller forehead motion angle 6.68°± 2.9 P  < 0.001. Females had more frequently straight horizontal forehead lines versus males: 68.4% vs 44.4% ( P  = 0.037). Young volunteers (<39.8 years) did not differ in their mean forehead motion angle when compared to older volunteers (>39.8 years): 13.70°± 9.0 vs 12.39°± 8.0 with P  = 0.530. Conclusion: Injections of neuromodulators in the forehead can be individualized by respecting the shape of the horizontal forehead lines. Wavy lines require injection points that are located more laterally, whereas straight lines require more centrally located injection points.